수술실에서 중심정맥관 삽입 시 번들적용이 중심정맥관 관련 혈류감염에 미치는 영향 - 신은정; 정재심; 최상호; 허인영 (Journal of Korean biological nursing science, 2016)
Background: This study purposed to examine how the incidence of the central line-associated bloodstream infection (CLABSI) in a operating room (OR) is affected by bundle application on central line insertion (CLI) practice. Methods: The study design was a pretest-posttest experimental trial. The subjects were 83 patients before the bundle application on CLI and 70 patients after. Results: The compliance(%) of bundle on CLI of among those who observed all of the five items increased from 7.2% before the intervention to 72.9% after. By items, compliance with the maximal barrier precaution was 100% for the use of a mask and cap before and after the intervention, but increased from 73.5% before the intervention to 88.6% after for the hand hygiene, from 73.5% to 88.6% for the use of a sterile gown, and from 9.6% to 75.7% for the use of a sterile large drape covering the whole body. CLABSI did not happen on CLI either before or after the application of the bundle intervention. Conclusion: Bundle application increased compliance with the use of a sterile gown and the use of a sterile large drape. However, its effect in the prevention of CLABSI was not clear probably due to the short period of intervention in a single hospital.